2020
DOI: 10.1007/s10840-020-00728-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute success and safety of the second-generation PVAC GOLD phased RF ablation catheter for atrial fibrillation

Abstract: Purpose The second-generation multi-electrode catheter, pulmonary vein ablation catheter (PVAC) GOLD, was designed to improve the delivery of phased radiofrequency energy and reduce procedure times using a 'single-shot' approach for pulmonary vein isolation (PVI), while retaining efficacy and safety. This large registry presents acute success rates and safety outcomes in a daily practice setting. Methods A total of 1017 patients undergoing first-time ablation for atrial fibrillation (AF) using PVAC GOLD were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A recently published large registry of 1,017 patients, reported that PVI was successfully achieved in 95-99% of paroxysmal, persistent and long-standing AF patients. Procedure times were reduced, and safety was maintained (38). Additional phased array products (Medtronic Inc., Minneapolis, MN, USA) include the Multi-Array Septal Catheter (MASC) and the Multi-Array Ablation Catheter (MAAC) which are designed to facilitate elimination of non-pulmonary vein triggers and arrhythmogenic substrates in the atria (38).…”
Section: Ablation Modalities: Comparative E Cacy and New Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published large registry of 1,017 patients, reported that PVI was successfully achieved in 95-99% of paroxysmal, persistent and long-standing AF patients. Procedure times were reduced, and safety was maintained (38). Additional phased array products (Medtronic Inc., Minneapolis, MN, USA) include the Multi-Array Septal Catheter (MASC) and the Multi-Array Ablation Catheter (MAAC) which are designed to facilitate elimination of non-pulmonary vein triggers and arrhythmogenic substrates in the atria (38).…”
Section: Ablation Modalities: Comparative E Cacy and New Techniquesmentioning
confidence: 99%
“…Procedure times were reduced, and safety was maintained (38). Additional phased array products (Medtronic Inc., Minneapolis, MN, USA) include the Multi-Array Septal Catheter (MASC) and the Multi-Array Ablation Catheter (MAAC) which are designed to facilitate elimination of non-pulmonary vein triggers and arrhythmogenic substrates in the atria (38). Pending additional investigation none of these products have received approval from the U.S. Food and Drug Administration (FDA).…”
Section: Ablation Modalities: Comparative E Cacy and New Techniquesmentioning
confidence: 99%
“…Simultaneously, it can map the pulmonary vein potentials, deliver diagnostic pacing stimuli, and verify the pulmonary vein post-treatment electrical isolation. It seems to allow for successful circumferential ablation of the pulmonary veins while reducing procedure times for patients with paroxysmal/persistent AF 58 .…”
Section: Radiofrequency Ablation-based Cathetersmentioning
confidence: 99%